Normativity and Practical Judgement - O'Neill, Onora (Journal of moral philosophy, 2007)
Abstract Norms are apt for reasoning because they have propositional structure and content; they are practical because they aim to guide action, rather than to describe aspects of the world. These two features hold equally of norms construed sociologically as the norms of specific social groups, and of norms conceived abstractly as principles of action. On either view, norms are indeterminate while acts are particular and determinate. Consequently norms cannot fully specify which particular act is to be done. Are they then not genuinely action-guiding unless supplemented by practical judgment? Yet accounts of practical judgement are often thin, sometimes seeing it as blind, unreasoned 'picking' of one rather than another enactment of a norm. However, on another view practical judgement carries the substantive task of seeking ways of acting that satisfy a plurality of norms, which can be both reasoned and practical.